AN ANALYSIS OF CULTURAL VALUES IN MALAYSIAN ENGLISH TEXTBOOK USED BY THE THIRD GRADERS OF PRIMARY SCHOOL - Axel Alessandro Satriawan (Faculty of Education and Teachers Training, 2020)
Malaysia is the country in the South East Asia that uses federal constitutional monarchy system which means it is a kingdom country. There are many diversities in Malaysia especially in culture. Moreover, culture plays an important role in society especially when it is together among people. Furthermore, knowing culture since youth is totally recommended in order to know how to deal it when facing the diversities because everyday people face the culture. That is why the kingdom put cultural values in the textbooks hoping that they learn them earlier and get better understanding. This study focuses on analyzing the cultural values of the Malaysian English textbook used by the third graders of primary school that are represented in it. The method of collecting the data is documentation. Moreover, the technique of analyzing the data is based on the Brown’s theory which uses checklist to evaluate the text book based on particular criteria. The steps in analyzing the data are (1) observing the textbook, (2) identifying the cultural values based on the Brown’s theory, (3) collecting the data, and (4) drawing the conclusion. The result of this study shows that there are six elements of cultural values represented in English Malaysian textbook used by the third graders of primary school in picture form (social organization (61%), custom & tradition (4%), religion (14%), art & literature (11%), form of government (1%), and economic system (9%)) while there are five elements of cultural values represented in sentence form (social organization (63%), custom & tradition (19%), art & literature (5%), economic system (13%), and language (1%)). There are 46 pictures and 120 sentences identified which contain the elements of cultural values. As a conclusion, the cultural values that are represented in the books are found in two forms, in pictures and in sentence forms in which each form has different frequency of the cultural values that appear in the book. At last, the suggestions are given to the author of Malaysian English Textbook for balancing the cultural values that are represented in the book.